Oncolytic alphavirus-induced extracellular vesicles counteract the immunosuppressive effect of melanoma-derived extracellular vesicles - Bhatt, Darshak K.; Boerma, Annemarie; Bustos, Silvina Odete; Otake, Andréia Hanada; Murillo Carrasco, Alexis Germán; Reis, Patrícia Pintor [UNESP]; Chammas, Roger; Daemen, Toos; Andrade, Luciana Nogueira de Sousa (Springer Nature, 2025)
Extracellular vesicles (EVs)-mediated communication by cancer cells contributes towards the pro-tumoral reprogramming of the tumor microenvironment. Viral infection has been observed to alter the biogenesis and cargo of EVs secreted from host cells in the context of infectious biology. However, the impact of oncolytic viruses on the cargo and function of EVs released by cancer cells remains unknown. Here we show that upon oncolytic virotherapy with Semliki Forest virus-based replicon particles (rSFV), metastatic melanoma cells release EVs with a distinct biochemical profile and do not lead to suppression of immune cells. Specifically, we demonstrate that viral infection causes a differential loading of regulatory microRNAs (miRNAs) in EVs in addition to changes in their physical features. EVs derived from cancer cells potentially suppress splenocyte proliferation and induce regulatory macrophages. In contrast, EVs obtained from rSFV-infected cells did not exhibit such effects. Our results thus show that rSFV infection induces changes in the immunomodulatory properties of melanoma EVs, which may contribute to enhancing the therapeutic efficacy of virotherapy. Finally, our results show that the use of an oncolytic virus capable of a single-round of infection allows the analysis of EVs secreted from infected cells while preventing interference from extracellular virus particles.
Keywords: Extracellular vesicles; Immunomodulatory; Melanoma; Oncolytic virus